Glowing in the dark: case report of a clue-poor melanoma unmasked by polarized dermatoscopy - Yoon K. Cohen; David J. Elpern; Dean Wolpowitz; Cliff Rosendahl (Mattioli1885, 2014)
We report a case of a melanoma arising in a congenital-type compound nevus, which was excised because it was observed by both the patient and the treating dermatologist to have changed. Because the lesion was routinely photo-documented with both polarized and non-polarized dermatoscopy images prior to excision, these images were available for subsequent examination. Matched images are presented in what appears to be unique in the published literature: polarizing-specific white lines are identified as a compelling clue to the diagnosis of melanoma in a lesion that contains no clues apparent in the non-polarized image. Dermatopathology images reveal that the melanoma is arising in conjunction with a congenital type nevus. As expected, dermatoscopic polarizing-specific white lines are evident on the melanoma but not the nevus, and while a possible explanation is discussed, this remains speculative.